Speaking Beyond the Classroom: Students’ Experiences with Task-Based Language Teaching in an Extracurricular Program - Kurnihayati; Teni Hadiyani; Siti Fatimah (STIT Buntet Pesantren Cirebon, 2026)
This study was motivated by the persistent challenges faced by EFL students in developing speaking skills, despite the importance of speaking for meaningful communication. Previous studies have shown that students often experience limited vocabulary, low confidence, and speaking anxiety, while research on the implementation of Task-Based Language Teaching (TBLT) in extracurricular contexts remains limited. Therefore, this study aimed to explore students’ learning experiences, perceived strengths, and challenges in the implementation of TBLT within an extracurricular English program. The study employed a qualitative case study design conducted in a Corporate Social Responsibility (CSR)-based extracurricular English program at SMP Negeri 1 Gempol. The participants were grade VIII and IX students with A1–A2 English proficiency levels. Data were collected through classroom observations, students’ responses, and program documentation, and analyzed using thematic analysis. The findings revealed that TBLT created a supportive and engaging learning environment that enhanced students’ participation, confidence, and willingness to speak through meaningful communicative tasks. However, several challenges were identified, including inconsistent attendance, learner fatigue after formal schooling, and differences in language proficiency. The study recommends more adaptive and flexible task design to support TBLT implementation in non-formal EFL learning contexts